The membrane QmoABC complex interacts directly with the dissimilatory adenosine 5´-phosphosulfate reductase in sulfate reducing bacteria - Ramos, Ana R.; Keller, Kimberly L.; Wall, Judy D.; Pereira, Inês A. C. (Frontiers in Microbiology, 2012)
The adenosine 5’-phosphosulfate reductase (AprAB) is the enzyme responsible for the reduction of adenosine 5’-phosphosulfate (APS) to sulfite in the biological process of dissimilatory sulfate reduction, which is carried out by a ubiquitous group of sulfate reducing prokaryotes. The electron donor for AprAB has not been clearly identified, but was proposed to be the QmoABC membrane complex, since an aprBA-qmoABC gene cluster is found in many sulfate-reducing and sulfur-oxidising bacteria. The QmoABC complex is essential for sulfate reduction, but electron transfer between QmoABC and AprAB has not been reported. In this work we provide the first direct evidence that QmoABC and AprAB interact in Desulfovibrio spp., using co-immunoprecipitation, cross-linking Far-Western blot, tag-affinity purification and surface plasmon resonance studies. This showed that the QmoABC-AprAB complex has a strong steady-state affinity (KD = 90 ± 3 nM), but has a transient character due to a fast dissociation rate. Far-Western blot identified QmoA as the Qmo subunit most involved in the interaction. Nevertheless, electron transfer from menaquinol analogues to APS through anaerobically purified QmoABC and AprAB could not be detected. We propose that this reaction requires the involvement of a third partner to allow electron flow driven by a reverse electron bifurcation process i.e. electron confurcation. This process is deemed essential to allow coupling of APS reduction to chemiosmotic energy conservation.